2020
DOI: 10.1002/fsn3.1409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of superfine grinding on physicochemical and antioxidant properties of soybean residue powder

Abstract: Soybean residue is an underutilized, nutrient‐rich by‐product of soybean processing. To enhance its value, we subjected soybean residue to superfine grinding and measured the resulting physiochemical properties and antioxidant activities. We prepared powders with particle sizes of 115.35, 77.93, 39.38, 25.01, and 20.44 μm. As particle size decreased, the surface area (from 96.46 to 198.32 m2/kg) and swelling capacity (from 2.05 to 10.62 ml/g) increased. Conversely, we observed decreases in the surface‐number m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 30 publications
1
32
1
Order By: Relevance
“…Analysis of the distribution of the UMF particle sizes obtained via the airflow ultrafine-grinding methods ( Figure 1 ) showed them to be between 10 μm and 80 μm, demonstrating them to be within the size range of ultrafine powder [ 33 ].Furthermore, the Dv values of the Tartary buckwheat samples are summarized in Table 1 . Generally, D10, D50, and D90 are used to characterize particle size distributions, and are the equivalent volume diameters at 10%, 50% and 90% of the cumulative volume, respectively [ 34 ]. It was found that the mean particle size of the TBCF was 100 μm, which was almost three times, five times, and two times that of the UMF for D10, D50, and D90, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the distribution of the UMF particle sizes obtained via the airflow ultrafine-grinding methods ( Figure 1 ) showed them to be between 10 μm and 80 μm, demonstrating them to be within the size range of ultrafine powder [ 33 ].Furthermore, the Dv values of the Tartary buckwheat samples are summarized in Table 1 . Generally, D10, D50, and D90 are used to characterize particle size distributions, and are the equivalent volume diameters at 10%, 50% and 90% of the cumulative volume, respectively [ 34 ]. It was found that the mean particle size of the TBCF was 100 μm, which was almost three times, five times, and two times that of the UMF for D10, D50, and D90, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, superfine powders possess more suitability in manufacturing of convenient and instant foods owing to improved solubility, oil and water holding capacities. In recent years, superfine grinding has been reported to increase antioxidant compounds and possible reason for this was attributed to alteration of solution behavior and molecular weight of bioactive compounds because of superfine grinding (Li et al 2020;Zhao et al 2015a, b). Although several studies have investigated the chemical composition and health functionalities of the Sanchi flower (Ng 2006;Zhu et al 2005), however, reports on exerted effects of superfine grinding Sanchi flower powders (SFP) properties are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is still highly nutritious (okara contains approximately, 50% fiber, 25% of proteins, 10% of lipids as well as a plethora of other useful compounds such as isoflavones, phytates, lignins, saponins, coumestans as well as phytosterols) and studies have found that it is a source of antioxidants and can be potentially used as weight-loss dietary supplements. Every year, large amount of okara are disposed worldwide in incineration plants and landfills with more than 2.8 million tonnes produced in China's tofu industry alone (Li, Guo, Gao, Wang, & Sun, 2020). It is estimated that almost 14 million tonnes of okara are produced around the world annually (Mok, Tan, Lee, Kim, & Chen, 2019).In human nutrition, probiotics are defined as live microorganisms in food ingredients that have specific health benefits when consumed in adequate amount (Afzaal et al, 2020).…”
mentioning
confidence: 99%